2018
DOI: 10.1155/2018/7060654
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Spinal Cord Injury without Radiographic Abnormality

Abstract: “Spinal Cord Injury without Radiographic Abnormality” (SCIWORA) is a term that denotes objective clinical signs of posttraumatic spinal cord injury without evidence of fracture or malalignment on plain radiographs and computed tomography (CT) of the spine. SCIWORA is most commonly seen in children with a predilection for the cervical spinal cord due to the increased mobility of the cervical spine, the inherent ligamentous laxity, and the large head-to-body ratio during childhood. However, SCIWORA can also be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 41 publications
1
48
0
11
Order By: Relevance
“…SCIWORA accounts for 1-10% of the spinal cord injury in children. Gregory et al [5] reported 0.08%cases in a multicentric study on about 34069 patients., SCIWORA is more common in children than adult with literature reports of 13 to 19% and 10 to 12% of children and adult spinal cord injuries respectively [6,8,9] The trauma causing SCIWORAs may not be of high intensity only, it may be trivial also. This is widely illustrated in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…SCIWORA accounts for 1-10% of the spinal cord injury in children. Gregory et al [5] reported 0.08%cases in a multicentric study on about 34069 patients., SCIWORA is more common in children than adult with literature reports of 13 to 19% and 10 to 12% of children and adult spinal cord injuries respectively [6,8,9] The trauma causing SCIWORAs may not be of high intensity only, it may be trivial also. This is widely illustrated in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that CSCIWFD is related to cervical spine degeneration and other factors, leading to a reduction in the effective cervical canal volume. However, the specific pathogenesis and treatment of this disease remain topics of debate [17,18]. Most researchers support surgical treatment and believe that surgery can reduce spinal cord edema, spinal canal decompression, improve spinal cord blood circulation, restore cervical spine stability, avoid and reduce secondary spinal cord injury, and facilitate spinal cord function recovery [19].…”
Section: Discussionmentioning
confidence: 99%
“…These include spinal cord traction and injury due to hyperflexion or hyperextension and parenchymal damage from edema or vascular injury. 57,63,64 It is conceivable that SCIWORA is seen less frequently in adults as a result of age-related changes in bone morphology and a decrease in ligamentous laxity. Preexisting degenerative changes to the spine, such as posterior vertebral spurs, ligamentum flavum bulging, and decreased vertebral body height are frequently found in adults presenting with a clinicoradiological mismatch.…”
Section: ) Pathophysiology and Mechanisms Of Injurymentioning
confidence: 99%
“…Published reports indicate that patients with SCIWORA may present with a wide range of symptoms, including different level of lower and upper extremity weakness, sensory loss, paresthesia, changes in tendon reflexes, loss of bladder and bowel function, signs of anterior/central/posterior cord or Brown-Sequard syndrome. 57,67 Boese and Lechler 55 showed that adults most commonly presented with American Spinal Injury Association (ASIA) grade C (39.7%) and grade D (22.8%). 13 Patients with suspected SCI should first be checked with direct radiograms and CT scans.…”
Section: ) Diagnostic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation